Application of PROMICE Q‐Transect in Situ Accumulation and Ablation Measurements (2000–2017) to Constrain Mass Balance at the Southern Tip of the Greenland Ice Sheet. Issue 6 (5th June 2018) - Hermann, Mauro; Box, Jason E.; Fausto, Robert S.; Colgan, William T.; Langen, Peter L.; Mottram, Ruth; Wuite, Jan; Noël, Brice; van den Broeke, Michiel R.; van As, Dirk
Abstract : With nine southern Greenland ice sheet ablation area locations, the Programme for Monitoring of the Greenland Ice Sheet (PROMICE) "Q‐transect" is a source of snow accumulation and ice ablation data spanning 17 years (2000 to present). Snow water equivalence measurements below equilibrium line altitude enable resolving the location and magnitude of an orographic precipitation maximum. Snow depth skillfully predicts snow water equivalence in this region, for which we find no evidence of change 2001–2017. After describing observed accumulation and ablation spatiotemporal patterns, we examine surface mass balance (SMB) in 5.5‐km HIRHAM5, 7.5‐km Modèle Atmosphèrique Régional (MAR) v3.7, and 1‐km Regional Atmospheric Climate Model (RACMO2.3p2) regional climate model (RCM) output. HIRHAM5 and RACMO2.3p2 overestimate accumulation below equilibrium line altitude by 2 times. MAR SMB is closer to observations but lacks a distinct orographic peak. RCM ablation underestimation is attributable to overestimated snowfall (HIRHAM5 and RACMO2.3p2), overestimated bare ice albedo (MAR), and underestimation of downward turbulent heat fluxes. Calibrated ablation area RCM SMB data yield −0.3 ± 0.5 Gt/a SMB of the 559‐km 2 marine‐terminating Sermilik glacier (September 2000 to October 2012). Using Enderlin et al. (2014, https://doi.org/10.1002/2013GL059010 ) ice discharge data, Sermilik glacier's total mass balance is −1.3 ± 0.5 Gt/a with interannual variability dominated by SMB. The area specific mass loss is 17 to 20 times greater than the whole ice sheet mass loss after Andersen et al. (2015, https://doi.org/10.1016/j.epsl.2014.10.015 ) and Colgan et al. (2015, https://doi.org/10.1016/j.rse.2015.06.016 ), highlighting the Q‐transect's situation in an ice mass loss hot spot. Key Points: Surface mass balance dominates the interannual variability in Sermilik glacier total mass balance South Greenland ice sheet accumulation and ablation observations reveal Sermilik glacier total mass loss being 20 times the Greenland ice sheet average Three RCMs underrate melt below ELA due to some combination of overestimated snowfall and ice albedo and underestimated downward turbulent heat flux